Analysis of Growth Strategy at Wuling Motors Makassar As A Response to Facing Economic Globalization Challenges - Dafitri Anggika; Asty Almaida; Abdul Rahman Kadir (Eduvest - Journal of Universal Studies, 2024)
Growth Strategy Analysis at the Wuling Motors Kumala Makassar Company as a Response to Facing the Challenges of Economic Globalization, is a research to get an overview of the company's internal strengths, market opportunities, company potential based on internal and external factors, as well appropriate growth strategies for carried out in operating the company. The aim of this research is to determine the company's response to facing the challenges of economic globalization that occur in Indonesia, especially in the automotive market segment in the marketing area of South Sulawesi, and Indonesia in general. This research method uses a qualitative approach, where the theoretical basis used refers to the opinions of several experts, in the form of books, journals, articles and other scientific writings related to this research. The data analysis used in this research is SWOT analysis (Rangkuti, Freddy. 2006. "SWOT Analysis Technique for Dissecting Business Cases: Reorienting Strategic Planning Concepts to Face the 21st Century"). From this research, the results obtained show that the Wuling Motors Kumala Makassar company is currently in a major strongth with large market opportunities, where the company's current position is also showing good growth. Based on this, the Wuling Motors Kumala Makassar company can implement an intensive growth strategy with differentiation, namely selling the latest Wuling car products, both in terms of technology, models and cheap prices offered as one of the responses to challenges of globalization economy in Indonesia.